Thymic extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue: a gene methylation study. Issue 8 (August 2013) - Takino, Hisashi; Li, Chunmei; Yamada, Seiji; Sato, Fumihiko; Masaki, Ayako; Fujiyoshi, Yukio; Hattori, Hideo; Inagaki, Hiroshi
Abstract Although rare, thymic mucosa-associated lymphoid tissue (MALT) lymphoma is considered to be a distinct clinicopathological entity. Using a methylation-specific polymerase chain reaction, we analyzed thymic MALT lymphomas (n = 18) for their methylation of the following seven tumor suppressor genes: DAPK1, p16INK4A, p14ARF, CDH1, RARB, TIMP3 and MGMT. Reactive lymph nodes (n = 16) were used as a control. Of the seven genes examined, thymic MALT lymphomas had an increased number of genes that were methylated (2.9 genes) as compared with reactive lymph nodes (0.63, p = 0.0003). In particular, thymic MALT lymphomas showed a frequent methylation of DAPK1, CDH1, TIMP3 and p14ARF. In addition, gene methylation of p14ARF was associated with a larger tumor size, while that of the other three genes was not associated with any clinicopathological features examined. This study suggests that methylation of tumor suppressor genes may play an important role in thymic MALT lymphoma.